2012
DOI: 10.1128/aem.01440-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonal and Geochemical Changes on the Geomicrobiology of an Iron Carbonate Mineral Water Spring

Abstract: Fuschna Spring in the Swiss Alps (Engadin region) is a bicarbonate iron(II)-rich, pH-neutral mineral water spring that is dominated visually by dark green microbial mats at the side of the flow channel and orange iron(III) (oxyhydr)oxides in the flow channel. Gradients of O 2 , dissolved iron(II), and bicarbonate establish in the water. Our goals were to identify the dominating biogeochemical processes and to determine to which extent changing geochemical conditions along the flow path and seasonal changes inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Other studies on FeOB communities (both neutrophilic and acidophilic) have observed general changes in community structure that correspond with temperature, season or rain (Edwards et al, 1999;Hegler et al, 2012;Johnson et al, 2012). In particular, Gault et al (2012) sampled a spring-fed iron mat in Chalk River, Ontario, once during each major season, and noted that the abundance of Gallionellales clones was greater in winter than in summer, consistent with the findings presented here.…”
Section: Discussionsupporting
confidence: 79%
“…Other studies on FeOB communities (both neutrophilic and acidophilic) have observed general changes in community structure that correspond with temperature, season or rain (Edwards et al, 1999;Hegler et al, 2012;Johnson et al, 2012). In particular, Gault et al (2012) sampled a spring-fed iron mat in Chalk River, Ontario, once during each major season, and noted that the abundance of Gallionellales clones was greater in winter than in summer, consistent with the findings presented here.…”
Section: Discussionsupporting
confidence: 79%
“…These bacteria face the problem that, at neutral pH, the abiotic reaction of oxygen and Fe(II) is fast. Therefore, bacterial Fe(II) oxidation with O 2 at neutral pH is limited to micro-oxic ([O 2 ] Ͻ 50 M) conditions, where microbial iron oxidation can compete favorably with the [O 2 ]-limited abiotic reaction (13,14). Favorable conditions for the growth of microaerophilic Fe(II) oxidizers are found in opposing gradients of Fe(II) and O 2 , e.g., in the oxicanoxic transition zone in sediments or groundwater seeps (15).…”
mentioning
confidence: 99%
“…Molecular ecology studies of temperate iron mats generally report that cyanobacteria make up a small percentage of the population (26,27). A recent study of an alpine spring (Fuschna Spring) in Switzerland found an interesting spatial relationship between a phototrophic iron mat that grew along the edge of the spring channel and an iron mat that grew in its center (28). Despite being separated by a centimeter or less, the populations in the phototrophic mat were quite unique from those in the iron mat community, indicating that there might be close physical proximity of the different communities without much intermixing of populations.…”
Section: Discussionmentioning
confidence: 99%